Anthropometric indices and their relationship with poor prognosis in patients with coronary artery disease and obesity - A. V. Svarovskaya; O. A. Trubacheva; S. V. Pereverzev; A. A. Garganeeva (Российский кардиологический журнал, 2022)
Aim. To assess the association of anthropometric indices in patients with coronary artery disease (CAD) and obesity and to study their predictive value in the development of adverse cardiovascular events.Material and methods. The study included 229 patients with CAD (median age, 55±7,56 years). Depending on the presence of obesity according to the World Health Organization criteria (1999), patients were divided into 2 groups. The 1st group included 107 obese patients, while the 2nd group — those without obesity (n=122). The groups were comparable in age. We measured waist (WC) and hip circumference (HC), followed by waist-to-hip ratio and body mass index calculation. The lipid profile parameters were determined by the enzymatic colorimetric method. During the study, the following indices were calculated: body mass index, visceral adiposity index, insulin resistance index, body shape index (BSI), fasting triglyceride (TG)/plasma glucose index, waist-to-height ratio, lipid accumulation product, TG-to-high density lipoprotein cholesterol ratio.Results. During the follow-up period, adverse cardiovascular events in the 1st group of patients were found in 37 (34,5%) patients, while in the 2nd group, the composite endpoint was revealed in 12,3% of patients. In order to develop a model for predicting the risk of an unfavorable CAD course in obese patients, we performed a logistic regression analysis, which showed that the following were the most significant predictors of unfavorable cardiovascular outcomes: TG/glucose index and BSI.Conclusion. Thus, of all the considered anthropometric indices, only two were associated with unfavorable CAD course — TG/glucose index and BSI. The data obtained indicate the validity of the search for novel useful obesity indicators with a good predictive value.